How to improve participation in social assistance programs - David Ribar (IZA World of Labor, 2014)
Social assistance programs are intended to improve people's well-being. However, that goal is undermined when eligible people fail to participate. Reasons for non-participation can include inertia, lack of information, stigma, the time and "hassle" associated with applications and program compliance, as well as some programs' non-entitlement status. Differences in participation across programs, and over time, indicate that take-up rates can respond both positively and negatively to policy change. However, there are clearly very identifiable ways in which relevant agencies can improve take-up.
Keywords: I38; 330; social assistance; program participation; administration